The Australian Series System - Smith, Clive (Archivaria, 1995)
The series system, as developed by the Australian Archives in the 1960s (and in full bloom in the 1970s, when the author joined the Australian Archives) is a complex and comprehensive system for managing records throughout their life cycle. Records were customarily surveyed while still in current use. The series descriptions prepared became the basis of all subsequent action, including disposal arrangements, transfer of custody, accessioning, location control, de-accessioning and destruction (where appropriate), access control, retrieval, and reference. This paper discusses only the author's views of the origin of the system and the links between the most important elements of the system: series and agencies. RÉSUMÉ Le système des séries tel que développé par les Australian Archives durant les années 1960 (et en plein essor durant les années 1970 lorsque l'auteur se joignit à cette institution) constitue un système vaste et complexe de gestion des documents tout au long de leur cycle de vie. Les documents étaient habituellement examinés pendant leur phase active. Les descriptions préparées pour les séries devinrent le fondement de toutes les autres interventions subséquentes incluant le protocole de disposition, le transfert de responsabilité, l'enregistrement, l'inventaire topographique, la restitution, la destruction (le cas échéant) la communicabilité, le repérage, et la référence. Cet article ne présente que la vision de l'auteur de l'origine du système ainsi que des liens entre les principaux éléments du système, c'est-à-dire la série et le créateur de documents.